The Mechanical Performance of Polymer Concrete Incorporating Waste Tin Fibres - Ashkan H.; Norhisham S.; Bakar M.S.A.; Syamsir A.; Abdullah M.J.; Asyraf M.R.M.; Chairi M.; Yetrina M.; Melasari J.; Farid M. (Universiti Putra Malaysia Press, 2025)
Concrete is the most widely used construction material in the world. It is now possible to construct structures out of concrete because this durable compound that consists of water, aggregate, and Portland cement not only gives us many scopes of design but also has a very high compressive strength at a low cost. This paper deals with alternative materials for the most common construction material, cement-based concrete and polymer concrete (PC), containing waste tin fibres. The study covers the fabrication of polymer concrete and the execution of three tests: compressive strength, flexural tensile, and splitting tensile. Tests were conducted to determine the mechanical properties of the PC, and the results were analysed and evaluated on several PC specimens with different ratios of waste tin fibre. The results showed that using waste tin as fibre reinforcement in PC would substantially enhance the overall mechanical performance. Specifically, the optimum amount of waste tin as reinforcement in PC was 0.16% for compressive and splitting tensile strengths, while 0.20% was the optimum fibre loading for the flexural tensile strength. In this case, a positive outcome was found at a constant resin-to-filler ratio of 40:60 by volume and a matrix-to-aggregate ratio of 1:1.35 by weight. ? Universiti Putra Malaysia Press.